An Exploratory Study of the Social Contract of Research and Innovation in Africa - Kahn, Michael Jeffrey (Frontiers in Research Metrics and Analytics, 2022)
This exploratory study adds to the under-developed literature on a Research Topic that laden with epistemological, philosophical, and ideological overtones, and that begs many questions. The literature on political economy generally, and that for Africa, enjoys full disciplinary status. In contrast the political economy of research and innovation remains an emerging interdisciplinary field that examines the overlap between innovation studies and political economy. The pursuit of ‘science and technology’ was expected to play its part in the imperialist and colonial agendas, and in the post-colonial project, when science and technology policy was a strong element in advocacy for Africa’s post-independence development. What have the policies achieved, and what explains the shortfalls? What indeed is the relationship between industrial policy and research and innovation policy? What is the social contract with research and innovation? The study commences with a general overview of the social contract for science before turning to Africa’s post-independence modernising agenda, and the roles ascribed to industrial policy and research and innovation policy. An eclectic methodology drawing on Cloutier (2021) is deployed to characterise and measure the social contract between research and innovation. The methodology adapts Cloutier (2021) to the functionality of national innovation systems. The responsiveness of STI policy is further probed using Martin’s (2015) categorisation of innovation policy informed by Theory of Change. Where possible reference is made to conventional STI indicators. Research and innovation policy is then assessed at continental and national levels, with attention given to the extent of linkages in national innovation systems. Further to tease out the various forms of social contract, five country-level STI policies are analysed using the Martin categorisation and Theory of Change methodology. It will be argued that a binding, social contract for inclusive research and innovation policy is largely absent, so that the prospects for attaining the SDGs remain elusive. Post Glasgow COP-26, donor pressure might be re-oriented to promote engagement with the Sustainable Development Goals, though the upholding research sovereignty could mitigate against this. Africa might rightly chide against such pressure, given her experience of what has been labelled as ‘vaccine apartheid.’